The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/rmv.1877
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive dengue outbreaks in East Africa: A proposed phased mitigation approach may reduce its impact

Abstract: Dengue outbreaks have persistently occurred in eastern African countries for several decades. We assessed each outbreak to identify risk factors and propose a framework for prevention and impact mitigation. Seven out of ten countries in eastern Africa and three islands in the Indian Ocean have experienced dengue outbreaks between 1823 and 2014. Major risk factors associated with past dengue outbreaks include climate, virus and vector genetics and human practices. Appropriate use of dengue diagnostic tools and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…Dengue infection can induce high fever and has been repeatedly detected in East Africa starting in 1982 (Baba et al, 2016;Johnson et al, 1982;Mease et al, 2011). Its detection in febrile Kenyan adults sampled for this study is also consistent with its detection in an outbreak reported from Mombasa, Kenya in 2013 (Ellis et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Dengue infection can induce high fever and has been repeatedly detected in East Africa starting in 1982 (Baba et al, 2016;Johnson et al, 1982;Mease et al, 2011). Its detection in febrile Kenyan adults sampled for this study is also consistent with its detection in an outbreak reported from Mombasa, Kenya in 2013 (Ellis et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This did not only distribute evidence more widely, but also produced explicit rather than evidence idleness [8,12]. Eventually, evidence management and sharing process thus became responsible to drive the shared behavioural changes and best practices with an understanding at the same time, important to improve of the overall preparedness, emergency response to care service delivery for impact [17,27].…”
Section: Promoting Evidence-based Translation Into Public Policies Anmentioning
confidence: 99%
“…Translation of knowledge-based in meeting the public needs, aspirations and expectations should be made clear at the outset, but understanding and trust may develop over time through seeing tangible benefits/gains from the collaborative endeavor [8,9]. Moreover, mutual and participative learning and better appreciation about each other's perspectives and contributions may lead to optimization on the full capacities and potential of all stakeholders to better preventive and curative processes and outcomes through the generation of more relevant and applicable knowledge.…”
Section: Value Of Evidence-based Contextual Translation and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations